The Politics of Trade Liberalization in the Presence of FDI Incentives - Andréa M. Maechler (Swiss National Bank, Study Center Gerzensee, 2000)
This paper examines whether inward FDI incentives can soften the political constraints associated with trade liberalization. After introducing the role of capital inflows into the political economy of trade framework pioneered by Grossman and Helpman (1994, 1995 and 1996), the paper traces the effects of FDI incentives on the politically sustainable equilibrium level of trade protection. In particular, the paper shows that FDI incentives reduce the politically sustainable level of trade protection when capital-owners are politically organized, while they inhibit the process of trade liberalization when labor is the main influential political force. Welfare implications are also considered.
Keywords: 330; Auslandsinvestition; Anreiz; Handelsliberalisierung; Theorie